PENGARUH KONSENTRASI DAN LAMA PERENDAMAN KINETIN PADA PERBANYAKAN TUNAS DAN UMBI BIBIT GLADIOL (GLADIOLUS HYBRIDUS L.) - Sofiati, Vivi; Andalasari, Tri Dewi; Yusnita, Yusnita (JURNAL AGROTROPIKA, 2010)
The increasing number of Gladiol Flower demand every year in Indonesia is not comparable with the low productivity of Gladiol Edible root. The technique of growing stimulation by using growth controller essence becomes one alternative to increase the number of sprout and edible root of Gladiol. This research is being purposeful to know the concentrate, the long term of submersion, and the combination between the concentrate and the best long term kinetin submersion which could increase the number of sprout and edible root of Gladiol (Gladiolus hybridus L.). The treatment is done by factorial (3 x 2) in Perfect Disordered Group Arrangement with four times repetition. The first factor is kinetin concentrate, those are 30, 40, and 50 ppm, the second factor is the long term of kinetin submersion, and those are 24 and 48 hours. The result of the research shows that there is no real influence between the treatments of concentrate and the long term kinetin submersion. The percentage of germinated edible root, the number of edible root, the height of the plants, the number of leaves, the number of beet, the weight of beet, the diameter of beet, the number of beet offspring, the weight of the offspring, and the dry weight of one root of beets.Key words: kinetin, multiplication, Gladiolus